(untitled) (Journal of Philosophy Culture and Political Science, 2019)
rticle is devoted to the problem of spreading of religious teaching the Gospel in Kazakhstan. The surveying of works of the following churches is conducted: «Grace Good fortune» and «New life» which actively carry out missionary activity in spread Gospel doctrine in Kazakhstan. The purpose of these churches is involving of the people on Jesus way through doctrine Gospel distribution. The missionary activity of these religious associations are studied in absentia from authors and have their own assessment. Keywords: religious education, policy of Evangelization, missionary activity, Church, religious activity.